2015
DOI: 10.1007/s00228-015-1896-x
|View full text |Cite
|
Sign up to set email alerts
|

CYP2B6 rs2279343 polymorphism is associated with smoking cessation success in bupropion therapy

Abstract: We showed that patients with CYP2B6*4 (rs2279343) variant had lower success rate with bupropion. Likely, the CYP2B6*4 variant, which leads to a rapid predicted metabolic phenotype for the isoenzyme, influences the pharmacological activity of bupropion. Our finding suggests that CYP2B6*4 may be an important genetic marker for individualized bupropion pharmacotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
3
22
0
3
Order By: Relevance
“…These expectations may exceed the evidence supported by the present literature. It should be noted the use of pharmacogenetic testing as well as nicotine metabolic ratio has only just begun to predict successful smoking cessation in general [15][16][17][18]20,21], and has yet to be shown to do so in the AI/AN population specifically. However, the few concrete examples of pharmacogenetic testing altering clinical outcomes offer promise to cessation treatment adherence [16,17,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These expectations may exceed the evidence supported by the present literature. It should be noted the use of pharmacogenetic testing as well as nicotine metabolic ratio has only just begun to predict successful smoking cessation in general [15][16][17][18]20,21], and has yet to be shown to do so in the AI/AN population specifically. However, the few concrete examples of pharmacogenetic testing altering clinical outcomes offer promise to cessation treatment adherence [16,17,42].…”
Section: Discussionmentioning
confidence: 99%
“…Wide pharmacogenetic variation across racial and ethnic groups contributes to interindividual differences in drug metabolism, with implications for drug dosing, medication response and toxicity [19]. Particular genetic variants of CYP2A6, CYP2B6, CHRNA5-A3-B4, CHRNB2, CHRNA5, CHRNA4 as well as nico tine metabolic ratio, a genetically informed biomarker, have been found to predict successful smoking cessation and response to pharmacotherapy (e.g., nicotine replacement therapy, varenicline, bupropion) [15][16][17][18]20,21]. AI/AN people have been historically underrepresented in medical research and may be less likely to benefit from current pharmacogenetic research and recommendations [19,[22][23][24].…”
mentioning
confidence: 99%
“…In contrast to variants that decrease the function of CYP2B6, the CYP2B6*4 allele is associated with increased CYP2B6 activity . One study has suggested that carriers of the CYP2B6*4 allele have lower smoking cessation success rates (35.5%) compared to wild type (48%) …”
Section: Resultsmentioning
confidence: 99%
“…35 One study has suggested that carriers of the CYP2B6*4 allele have lower smoking cessation success rates (35.5%) compared to wild type (48%). 55…”
Section: Influence Of Cyp2b6 Genetic Variation On Pharmacodynamics mentioning
confidence: 99%
“…Likely, the CYP2B6*4 variant influences the pharmacological activity of bupropion, and CYP2B6*4 may be a genetic marker for individualized bupropion pharmacotherapy [98]. …”
Section: Genetics Of Smoking Cessation Treatment Responsementioning
confidence: 99%